A Pilot Randomized Trial of Community‐Based Parent Training for Immigrant Latina Mothers. Issue 1 (26th November 2013) - Williamson, Ariel A.; Knox, Lyndee; Guerra, Nancy G.; Williams, Kirk R.
Abstract: This paper reports on the development and piloting of the Madres a Madres (Mothers to Mothers) program, a new, community‐based parent training program designed for immigrant Latina mothers and their children. Promotoras, or female community health workers of Latina background, delivered the program in a home visitation format. A total of 194 mothers and 194 focal children (87 male, 107 female) ages 7–12 were randomized to the intervention (113 mother–child dyads) or wait‐list control condition (81 mother–child dyads) over the study period. Outcomes of interest were mother‐reported parenting skills, broad family functioning, and child externalizing and internalizing behaviors. Data collection occurred at pretest, 3‐month posttest, and 9‐month follow‐up periods. Multilevel growth models revealed increases in intervention mothers' reported parenting skills, family support, and family organization, and reductions in child internalizing behavior from pretest to follow‐up, relative to the control condition. Outcomes did not vary by focal child age, gender, nativity status, or mother acculturative status (years in the United States). Findings are discussed in the context of future directions for research on the Madres a Madres program and on the implementation and dissemination of empirically‐supported parent training practices to culturally diverse families.